Cryptococcus meningitis presented with multiple cerebral infarcts in an immunocompetent patient - ERTÜRK ŞENGEL, BUKET; TİGEN, ELİF; MİDİ, İPEK; ÇERİKÇİOĞLU, NİLGÜN; ODABAŞI, ZEKAVER (ELSEVIER SCI LTD, 2021)
Cryptococcus neoformans is generally observed with immunosuppressive conditions. Rarely, it may be seen in immunocompetent individuals and presented with non-specific conditions. We described an immunocompetent case of cryptococcal meningitis presented with multiple cerebral infarcts. Despite the late diagnosis and emergence of hydrocephalus during treatment, the patient was recovered without any sequelae. In immunocompetent patients, the conventional diagnostics tests may be negative because of the low fungal load. If it is available, the Biofire FilmArray meningitis panel has high sensitivity and specificity for diagnosis. (C) 2021 The Authors. Published by Elsevier Ltd.
Keywords: Cerebral infarct; Cryptococcus neoformans; Film array; Hydrocephalus; NEGATIVE PATIENTS; NEOFORMANS; INFECTION